Creating the birth. Reproductive values in the state of Chiapas - María Jesús Montes Muñoz; Graciela Freyermuth Enciso (Universidad de Alicante, 2012)
Characteristics that surround to the region of the tops of Chiapas have favored the isolation of many of their indigenous communities of which we gather its representations and practices on the reproduction's cares. We approached to the physical context and the life's conditions to be able to understand its cosmovision and later we have exposed the beliefs and activities that they have developed around the pregnancy, childbirth, puerperal and new born cares.